O niektórych strategiach ucieczkowych i kompensacyjnych w komunikacji chorych z otępieniem alzheimerowskim (Conversatoria Linguistica, 2019)
The article presents observations related to communication based on a dialog witha man diagnosed with dementia of the Alzheimer type (6 stage according to the Global DeteriorationScale). The essential aim of the research was to determine the range of possibilities andmeans of communication available to the patient. Attention was paid to the patient’s interactions,taking into account such aspects as supporting interaction and withdrawal from it. In thearticle the author presents some strategies of compensation and escapism that the patient usedduring conversations.